Are There Any Potential Health Risk of Heavy Metals Through Dietary Intake of Olive Oil that Produced In Morphou, Cyprus - Kabaran, Seray; Güleç, Atilla; Besler, Tanju Halit (Progress in Nutrition, 2020)
Background and Objective: The purpose of this study was to assess concentrations of heavy metals in olive oils, and to assess the potential health risks using the Daily Intake of Metal (DIM) and the Health Risk Index (HRI) of these metals via dietary intake of olive oil. Methods and Study Design: A total of 500 adults aged 30-49 years were included in the study to investigate the average dietary intake of olive oil, and the average body weight of the study population. In addition, a total of 27 natural olive oil samples were analyzed for heavy metals using Inductively Coupled Plasma-Mass Spectrometer with three replications. Concentrations of heavy metals were determined in olive oils produced in Morphou and Lefka. Furthermore, potential health risks of heavy metals via dietary intake of olive oil were calculated. Results: The results showed that the mean levels of 52Cr, 59Co, 60Ni, 75As, 111Cd, 208Pb, 57Fe, 65Cu, and 66Zn in the olive oil samples were 123.83±44.70 ng/ml, 0.81±2.20 ng/ml, 30.18±9.77 ng/ml, 0.87±1.46 ng/ml, 1.53±2.02 ng/ml, 27.72±28.77 ng/ml, 875.06±806.85 ng/ml, 7.85±13.54 ng/ml, and 469.36±312.86 ng/ml, respectively. Also, HRI was calculated as less than 1 for all heavy metals. Conclusions: According to the results of the current study, although health risk assessment showed no potential risk for the local population through the consumption of olive oil, it is very important to assess the health risks of ingesting heavy metals with dietary intake of other frequently consumed foods in the studied region.